Screening semen samples for Zika virus infection: role for serologic and RT-PCR testing - Humberto Ferraz; Humberto Ferraz; Humberto Ferraz; Kevan Akrami; Kevan Akrami; Kevan Akrami; Laise de Moraes; Laise de Moraes; Lais Cambuí Gusmão; Genevieve Coelho; Daniele Freitas; Daniele Freitas; et al. (Frontiers in Tropical Diseases)
IntroductionZika virus (ZIKV) is primarily transmitted through mosquito bites though may act as a sexually transmitted infection. Men can shed the virus in their semen for extended periods, with reports indicating shedding for up to six months after the initial infection. This poses a concern for couples planning pregnancy, whether through natural or assisted methods due to the risk of congenital Zika disease. Human reproductive clinics typically perform serologic tests to screen for Zika infection.MethodsIn this study, we evaluated semen samples stored in a human reproduction clinic in Salvador, Brazil, during the Zika virus outbreak, using real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR) technique.Results36 sperm samples from 23 donors were analyzed, including 5 with positive IgG serology for ZIKV and all negative for IgM. Despite these serologic findings, all analyzed samples were negative by RT-qPCR ZIKV.DiscussionDespite the limited number of samples, this study raises further concern that the use of serology may be an unreliable surrogate method to predict the presence of ZIKV in semen.